Pemanfaatan Limbah Cangkang Sawit dan Abu Cangkang Sawit Sebagai Material Inovatif Untuk Beton Berpori Ramah Lingkungan - Muhammad Arif (Universitas Sulawesi Barat, 2025)
Utilization of Palm Biomass Waste as Aggregate and Cement Substitute in Pervious Concrete. This study aims to evaluate the utilization of palm shell waste and palm shell ash as innovative materials in the production of environmentally friendly pervious concrete. The concrete mixtures were varied by replacing coarse aggregate with palm shell at 0%, 25%, and 50%, and partially replacing cement with palm shell ash at 10%. Tests were conducted to assess compressive strength, splitting tensile strength, density, total voids, permeability, and the ability to support grass growth. The results indicate that all pervious concrete variations did not meet the minimum compressive strength standard based on SNI 03-0691-1990. The addition of palm shell increased permeability and total void content, but decreased compressive strength, tensile strength, and density. Grass growth was more favorable in mixtures containing palm shell, indicating a positive ecological potential. Overall, the use of palm shell and palm shell ash shows potential for non-structural applications of pervious concrete where drainage performance and environmental sustainability are prioritized. However, it is not recommended for structural use due to the low mechanical strength obtained.